PENDETEKSIAN EXCHANGE MARKET PRESSURE DI KAWASAN ASEAN-5 (Pendekatan Model DCC MGARCH) - , ALIFAH ROKHMAH IDIALIS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this undergraduate thesis is to analyze and determine the exchange market pressure (EMP) in ASEAN-5. The EMP is detected through dynamic conditional correlation bertween exchange rate ASEAN-5 volatility. Dynamic Conditional Correlarion Multivariate GARCH (DCC MGARCH) is the method used in this thesis. The data of exchange rate ASEAN-5 is from International Financial Statistic data, such as Indonesia rupiah per US $, Filipina ringgit per US $, Thailand bath per US $, Malaysia ringgit per US $, and Singapura $ per US $. The analysis results show there is any dynamic conditional correlation between exchange rate ASEAN-5 volatility. It proves that there is EMP in ASEAN-5, caused by global financial crisis in 1997-1998 or 2008, or transmission of volatility spillover.